Topical therapies in psoriasis - R Torsekar; Manjyot M Gautam (Wolters Kluwer Medknow Publications, 2017)
Topical therapy as monotherapy is useful in psoriasis patients with mild disease. Topical agents are also used as adjuvant for moderate-to-severe disease who are being concurrently treated with either ultraviolet light or systemic medications. Emollients are useful adjuncts to the treatment of psoriasis. Use of older topical agents such as anthralin and coal tar has declined over the years. However, they are cheaper and can still be used for the treatment of difficult psoriasis refractory to conventional treatment. Salicylic acid can be used in combination with other topical therapies such as topical corticosteroids (TCS) and calcineurin inhibitors for the treatment of thick limited plaques to increase the absorption of the latter into the psoriatic plaques. Low- to mid-potent TCS are used in facial/flexural psoriasis and high potent over palmoplantar/thick psoriasis lesions. The addition of noncorticosteroid treatment can also facilitate the avoidance of long-term daily TCS. Tacrolimus and pimecrolimus can be used for the treatment of facial and intertriginous psoriasis. Tazarotene is indicated for stable plaque psoriasis usually in combination with other therapies such as TCS. Vitamin D analogs alone in combination with TCS are useful in stable plaques over limbs and palmoplantar psoriasis. Topical therapies for scalp psoriasis include TCS, Vitamin D analogs, salicylic acid, coal tar, and anthralin in various formulations such as solutions, foams, and shampoos. TCS, vitamin D analogs, and tazarotene can be used in the treatment of nail psoriasis.